ANTI-MICROBIAL SPECTRUM FOR BACTERIAL UROPATHOGENS IN ADULT PATIENTS ASSOCIATED WITH URINARY TRACT INFECTIONS AT GOVERNMENT TEACHING HOSPITAL - UJJWALA, V.; KAREEMULLA, SHAIK; CHELSIYA, K. BLESSY HEBSIBHA; ZEENTY, B.; REDDY, A. VENKATA SUBBA; REDDY, R. MADHAV (International Journal of Current Pharmaceutical Research, 2023)
Objective: Urinary tract infection (UTI) is one of the most common bacterial infections, affecting 150 million people each year worldwide. UTI’s are a significant cause of morbidity in females, infant boys and older men of all age groups. The most common causative agent for UTI is uropathogenic Escherichia coli. Patients suffering from symptomatic UTI are commonly treated with antibiotics. The present study was undertaken to find the etiology, risk factors, clinical pattern, isolated uropathogens and therapeutic profile of UTI. Methods: It was a prospective, observational, descriptive, cross-sectional study conducted for a period of 6 mo from April 2022 to September 2022 at RIMS, Kadapa. A total of 35 UTI patients were recruited based on study criteria. The data was collected, analysed, summarised as averages. Graph pad prism software was applied for statistics by using Microsoft excel. Fig. represented through bar graphs, pie charts. Results: In a total of 35 patients suffering from UTI, we found that 7 were males and 28 were females, based on age groups; 2 patients belong to 21-30 y and 18 patients belong to 31-40 y, 10 patients belong to 41-50 age group, 3 patients belong to 51-60 y. In a total of 82 risk factors 40% were diabetes mellitus, 20% were hypertension, 17% were renal calculi, 5% were cyanosis, 11% were BPH, 6% were ESRD. In a total of 95 clinical symptoms, we observed fever (32.5%) as a major symptom, followed by burning micturition (16.5%). Other signs like abdominal pain, urine urgency, hematuria were also reported. On assessing urine culture, uropathogens Escherichia coli (35%) was isolated in majority UTI cases followed by Staphylococcus aureus (17%), Pseudomonas aeruginosa (14%), Candida species (14%), Enterococcus faecium (11%), Proteus species (8%). Total drugs prescribed were 150. Fluoroquinolones (48 in number, 32%) were the most common prescribed antibiotic drug category, followed by Anti-mycobacterial (32 in number, 21%), Cephalosporins (25 in number, 17%), Penicillins (20 in number, 13%), Macrolides (14 in number, 10%), Combinational therapy (11 in number, 7%). Conclusion: The UTI prevalence was more in females at GGH–RIMS, Kadapa. E. coli was the most common species isolated in UTI patients. At research site, physicians frequently prescribed medications were Ciprofloxacin (fluoroquinolones) and Nitrofurantoin (anti-mycobacterial) for UTI patients.